ESG narrative and ESG performance :Talk or Walking the Talk? - Dai, Ting (Pacific International Journal, 2024)
The subject, text and object constitute the basic logical framework of narratology, the subject of the ESG narrative is listed companies, the text is ESG reports, corporate governance, and environment and society-related content in annual reports, and the object is stakeholders. This paper selects China’s A-share listed companies in 2018 2022 as the initial sample and represents the ESG narrative by selecting the ESG-related word frequency weights in the annual report of the enterprise in that year. The multiple regression model of ESG "consistency between words and deeds" is constructed by taking the ESG rating scores of CSI in the same year as the ESG performance of the enterprise. It is found that, firstly, there is indeed a "discrepancy between words and deeds" between corporate ESG narratives and corporate ESG performance, and corporations have a stronger tendency to exaggerate their CSR. Second, board size is positively related to corporate ESG "misrepresentation", and firm size has a particularly significant effect on the social dimension of corporate ESG performance.The above findings have some implications for our regulators: First, we should pay more attention to the social dimension of corporate ESG narratives, as listed companies often exaggerate their social responsibilities to improve their ESG performance. Second, more quantitative indicators should be used to evaluate the social dimension.